Common Florida Spiders - J.L. Castner (EDIS)
This document provides an overview of common spiders found in Florida, detailing their physical characteristics, behaviors, and habitats. It covers various species, including jumping spiders, crab spiders, golden silk spiders, spiny orb-weavers, black and yellow argiope spiders, green lynx spiders, wolf spiders, and long-jawed orb-weavers. Each section highlights unique features, such as the jumping spiders’ eye arrangement and hunting methods, the crab spiders’ camouflage, and the golden silk spiders’ large webs. The document aims to educate readers on identifying and understanding these arachnids. Date first printed: November 1992.